2019
DOI: 10.1007/s00784-019-03096-4
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent green tea effect on decrease of inflammation in human oral gingival epithelial keratinocytes: in vitro study

Abstract: Objectives This in vitro study aimed to analyze the anti-inflammatory and wound healing potential of green tea extract (GTE) in human gingival epithelial keratinocytes (HGEK) treated with lipopolysaccharides (LPS). Materials and methods A cell viability assay was conducted using MTT to determine nontoxic levels of GTE on immortalized HGEK. Cells were concomitantly treated with LPS (1 μg/ml) and GTE (1 mg/ml, 2.5 mg/ml, 5 mg/ml, and 10 mg/ml) to assess inflammation. Gene expression levels of inflammatory marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…In this study, the inflammatory cytokines (TNF-α, IFN-γ, IL-10, and IL-13) returned to control serum levels after SP and/or MGT treatment of S. mansoni-infected mice, demonstrating the anti-inflammatory effects of SP and MGT. Green tea and green tea flower extracts downregulate the expression of inflammation markers, including IL-β1, IL-6, and TNFα, in human gingival epithelial keratinocytes and mouse liver treated with lipopolysaccharides (69,70). Theanine, the main component of MGT, and its metabolites, such as glutamine and ethyleneimine, alleviate inflammation by reducing NF-κB activation and neutrophil accumulation in tissues and dampening the Ca 2+ channels to block inflammatory mediator release (71).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the inflammatory cytokines (TNF-α, IFN-γ, IL-10, and IL-13) returned to control serum levels after SP and/or MGT treatment of S. mansoni-infected mice, demonstrating the anti-inflammatory effects of SP and MGT. Green tea and green tea flower extracts downregulate the expression of inflammation markers, including IL-β1, IL-6, and TNFα, in human gingival epithelial keratinocytes and mouse liver treated with lipopolysaccharides (69,70). Theanine, the main component of MGT, and its metabolites, such as glutamine and ethyleneimine, alleviate inflammation by reducing NF-κB activation and neutrophil accumulation in tissues and dampening the Ca 2+ channels to block inflammatory mediator release (71).…”
Section: Discussionmentioning
confidence: 99%
“…EGCG has been shown to be anti-inflammatory by suppressing the synthesis and action of inflammatory pathway such as, peroxynitrite, nitric oxide synthase, reactive oxygen species, and also cyclooxygenase-2 [28]. On the other study, EGCG inhibited the levels of pro-inflammatory cytokines including TNF-α, IL-1β, and IL-6 [29].…”
Section: Anti-inflammatory Effect Of Egcgmentioning
confidence: 95%
“…A 250 ml cup of brewed green tea provides approximately 25-60 mg of EGCG (roughly 50-60% of the catechins are EGCG). In vitro, a study in human gingival epithelial keratinocytes (HGEK) treated with LPS showed that green tea extracts (2.5, 5, and 10 mg/ml) decreased IL-β1, IL-6 and TNFα gene expression by more than 10-fold (Hagiu et al, 2020). Another study in rats with acetic acid-induced colitis demonstrated that EGCG (50 mg/kg/day for seven days) exerts anti-inflammatory activity by inhibiting the production of TNFa, IFN-gamma and NF-kappaBp65 (Ran et al, 2008).…”
Section: Green Tea Polyphenols and Other Compoundsmentioning
confidence: 99%